Improving Seventh Grade Students’ Reading Comprehension of Fantasy Stories Through the SQ3R Method - Nila Tansil; Teguh Setiawan (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2026)
This classroom action research was conducted in response to seventh-grade students’ low comprehension of fantasy story texts, particularly their difficulty identifying textual elements, tracing characters and events, and interpreting implied meanings. The study aimed to improve both the learning process and students’ reading-comprehension outcomes through the Survey, Question, Read, Recite, and Review (SQ3R) method. The participants were 16 seventh-grade students at SMP Negeri 1 Karau Kuala, South Barito Regency. The study was implemented in two cycles, each comprising planning, action, observation, and reflection. Data were collected through student-activity observation sheets, reading-comprehension assessment sheets, field notes, and documentation, and were analyzed descriptively using qualitative and quantitative procedures. The findings showed progressive improvement in classroom participation and achievement. In Cycle I, the mean score for the observed attitude and activity indicators was 2.3, with a total score of 9.2. In Cycle II, the overall activity mean increased to 3.0, with a total score of 12.0. The mean reading-comprehension score increased from 55 in the pre-action stage to 65.6 in Cycle I and 72.8 in Cycle II. The percentage of students achieving mastery rose from 31% to 56% and then to 75%. These findings indicate that the structured SQ3R stages supported more active participation and improved reading comprehension in this classroom context.